ENTOMOFAUNA ASOCIADA AL MATORRAL COSTERO DEL NORTE CHICO - Solervicens, Jaime; Elgueta, Mario (Acta Entomológica Chilena, 2022)
(IV Región, Chile) was carried on. An annual cycle of monthly sampling was conducted from may 1985 to may 1986 with an additional sampling during oclober 1986. The 12 months sampling was climatologically characterized by extreme drought. The sampling method employed was by beating sheet. Three orders of insects were dominan! Coleóptera, Hymenoptera and Hemiplera. Spring time showed the more abundance of varied insects. The dislribution of insects in the host plants is thought to depend and be related to the plant cover and persistence of foliage, though its palatableness and lype of polinizaron are also influential. Most of the species caught are “generalists", but a few of them appears to be speciftcally associated to their host plants, especially in the case of Puya chilmsis, which is probably due to the more stable condition of the infrutescence which remain present all over the year. The occurrence of species of insects was compared with the phenological situation of the host plants to clear up their relations with the appearance of foliage and the blooming season.